Effects of tillage, mulch and irrigation on maize (Zea mays l.) yield in drought prone area (Bangladesh Journal of Agriculture, 2022)
The experiment was conducted to study the effect of tillage, mulch and irrigation on soil moisture, yield and yield attributes of hybrid maize (var. BARI Hybrid Maize-6). Two tillage practices (minimum tillage and conventional tillage), two levels of mulches (no mulch and rice straw mulch @ 3 t ha-1) and three irrigation frequencies (one irrigation at 32 days after sowing (DAS), two irrigations at 32 and 55 DAS and three irrigations at 32, 55 and 85 DAS were used as treatment variables. Twelve treatment combinations were assigned in a split-split plot design with three replications. Minimum tillage and mulch conserved more moisture than conventional tillage with no mulch in both years. Minimum tillage and mulch (rice straw) as well as irrigation at 32, 55 and 85 DAS gave higher grain yield than conventional tillage with no mulch and any level of irrigation. Results revealed that application of straw mulch along with three irrigations and any kind of tillage practice might be a suitable combination for obtaining higher yield of maize in drought prone area.Bangladesh J. Agri. 2022, 47(1): 27-38